Application of BRET to monitor ligand binding to GPCRs - Stoddart, Leigh A.; Johnstone, Elizabeth K.M.; Wheal, Amanda J.; Goulding, Joelle; Robers, Matthew B.; Machleidt, Thomas; Wood, Keith V.; Hill, Stephen J.; Pfleger, Kevin D.G. (Nature Publishing Group, 2015)
Bioluminescence resonance energy transfer (BRET) is a well-established method for investigating protein-protein interactions. Here we present a BRET approach to monitor ligand binding to G protein–coupled receptors (GPCRs) on the surface of living cells made possible by the use of fluorescent ligands in combination with a bioluminescent protein (NanoLuc) that can be readily expressed on the N terminus of GPCRs.